The EGR2 gene is involved in axonal Charcot−Marie−Tooth disease. (24th July 2015) - Sevilla, T.; Sivera, R.; Martínez‐Rubio, D.; Lupo, V.; Chumillas, M. J.; Calpena, E.; Dopazo, J.; Vílchez, J. J.; Palau, F.; Espinós, C.
Abstract : Background and purpose: A three‐generation family affected by axonal Charcot−Marie−Tooth disease (CMT) was investigated with the aim of discovering genetic defects and to further characterize the phenotype. Methods: The clinical, nerve conduction studies and muscle magnetic resonance images of the patients were reviewed. A whole exome sequencing was performed and the changes were investigated by genetic studies, in silico analysis and luciferase reporter assays. Results: A novel c.1226G>A change (p.R409Q) in the EGR2 gene was identified. Patients presented with a typical, late‐onset axonal CMT phenotype with variable severity that was confirmed in the ancillary tests. The in silico studies showed that the residue R409 is an evolutionary conserved amino acid. The p.R409Q mutation, which is predicted as probably damaging, would alter the conformation of the protein slightly and would cause a decrease of gene expression. Conclusions: This is the first report of an EGR2 mutation presenting as an axonal CMT phenotype with variable severity. This study broadens the phenotype of the EGR2 ‐related neuropathies and suggests that the genetic testing of patients suffering from axonal CMT should include the EGR2 gene.